Impact of chlorhexidine baths on suspected sepsis and bloodstream infections in hospitalized neonates in Zambia. (July 2020) - Westling, T.; Cowden, C.; Mwananyanda, L.; Kapasa, M.L.; Machona, S.; Pierre, C.; Mitra, N.; Hamer, D.H.; Coffin, S.E.
Highlights: Bathing infants with chlorhexidine reduced rates of bloodstream infection in NICUs. Antiseptic baths were not associated with any adverse events. Modern statistical methods provide interpretable estimates of causal effects. Abstract: Introduction: Sepsis is the leading cause of infectious morbidity and mortality among hospitalized neonates. In high-resource pediatric and adult intensive care units, use of aqueous chlorhexidine (CHG) solution has been associated with reduced risk of bloodstream infections (BSI). Objectives: To assess the impact of bathing of neonates with 2% CHG on BSI, suspected sepsis, and mortality in a low-income country neonatal care unit. Methods: We conducted a secondary analysis of data from the Sepsis Prevention in Neonates in Zambia (SPINZ) study, a prospective observational cohort study performed at a large public referral hospital in Lusaka, Zambia. The SPINZ study assessed the impact of an infection control bundle (consisting of alcohol hand rub, SMS hygiene reminders, enhanced environmental cleaning, and CHG baths for babies ≥1.5 kg) on sepsis, BSI, and all-cause mortality. Episodic shortages in study staffing resulted in some enrolled babies not receiving a CHG bath. Using Longitudinal Targeted Maximum Likelihood Estimation and Cox proportional hazards regression to adjust for observed confounding, we estimated the causal effect of receiving a CHG bath within the first 3 days of life on suspected sepsis, BSI, and death among inborn babies enrolled during the study implementation and intervention phases. Results: The majority of inborn, enrolled babies ≥1.5 kg received a CHG bath within 3 days of NICU admission (864 of 1233, 70%). We found that CHG bathing reduced the hazard rate of BSI among inborn babies ≥1.5 kg by a factor of 0.58 (p = 0.10, 95% CI: 0.31, 1.11), corresponding to an absolute risk reduction of 9.6 percentage points within a week of admission (p = 0.002, 95% CI: 3.4–15.7 percentage points). We did not find a statistically significant effect of CHG bathing on culture-negative sepsis (p = 0.54) or death (p = 0.85). Conclusion: In our single center study, CHG bathing at admission was associated with a reduced risk of BSI due to a pathogenic organism after adjusting for potential confounding. Our results suggest that CHG may be an effective intervention for preventing neonatal sepsis in high-risk, low-income country settings.